(untitled) (Asian Journal of Medical and Biological Research, 2025)
Antimicrobial drug residues in foods of animal origin pose a significant food safety and public health concern, contributing to antimicrobial resistance (AMR) in the food chain. In Bangladesh, the poultry industry is rapidly growing, yet there is minimal monitoring of antibiotic residues in retail products, coupled with low consumer awareness. This study aimed to assess the extent of fluoroquinolone and tetracycline residues in retail broiler liver samples and to evaluate the knowledge, attitudes, and practices (KAP) of consumers and vendors in Mymensingh, Bangladesh. The research was a cross-sectional study conducted between March and September 2018. Fifty broiler livers were purchased from four markets and screened for residues using thin-layer chromatography (TLC) with certified standards and predefined acceptance windows. Concurrent KAP interviews were conducted with 216 respondents, including 120 consumers and 96 vendors/handlers. The residue screening revealed that 45 out of 50 livers (90.0%; 95% CI 78.6–95.7) tested positive for at least one target class, with market-wise positivity ranging from 84.6% to 92.3%. Among the positive samples, bands consistent with ciprofloxacin were the most frequent, followed by oxytetracycline, doxycycline, and enrofloxacin. In the KAP survey, 39.8% of respondents demonstrated adequate knowledge (≥75% correct), 56.0% had favorable attitudes, and 36.6% reported appropriate practices. Vendors exhibited lower rates of appropriate practices compared to consumers (26.0% vs. 45.0%). Adequate knowledge (adjusted OR 3.72; 95% CI 2.02–6.86) and favorable attitudes (adjusted OR 2.41; 95% CI 1.29–4.52) were independently associated with appropriate practices. Additionally, markets with a higher mean vendor KAP index tended to have lower TLC positivity (Spearman ρ = −0.95; P = 0.051). Although TLC is qualitative and does not assess compliance with maximum residue limits (MRL), the high positivity rates indicate a substantial risk of consumer exposure at the point of sale. Targeted communication focused on vendor compliance with withdrawal periods, documentation/traceability, and standardized consumer advisories, alongside routine low-cost screening and confirmatory testing, could enhance stewardship and reduce downstream residues in this context. Asian J. Med. Biol. Res. 2025, 11(4), 114-124